Kurikulum Merdeka: Memperkuat Keterampilan Abad 21 untuk Generasi Emas - Juan Gabriel Mongkau; Richard Daniel Herdi Pangkey (Departement of Mathematics Education, 2024)
The formulation of the problem in this study is how the implementation of Independent curriculum and the impression of 21st century skills for the golden generation. In the education system, the curriculum is considered a central and fundamental element in learning, thus becoming a crucial aspect in education. The Merdeka curriculum in Indonesia aims to create a golden generation of global competitiveness. The Merdeka curriculum can be an effective strategy to strengthen 21st century skills for Indonesia's Golden Generation, focusing on developing students ' potentials and skills, character education, and collaboration among all parties. The method in this research literature or literature review. A) determine the research topic of teaching 21st century skills in Primary School; b) search and collect various articles from Scopus website, Google Scholar and other journals; c) classify articles related to different types of research topics, d) synthesize relevant articles, noting the key points in each article; and e) write articles on synthetic results. Qualitative methods are used in data analysis methods. The Independent curriculum provides support for the development of each individual's potential and skills to strengthen character and prepare students to acquire the skills needed in global competition.